Percepción de la reflexión docente en un grupo de maestros de una escuela pública de Ayacucho - Reynaldo Vicente Alberca La Torre; Susana Frisancho (Pontificia Universidad Católica del Perú, 2011)
Perceptions of Teacher Reflection Among a Group of Public School Teachersin Ayacucho The goal of this study was to explore beliefs about pedagogical reflection held by teachers in an Ayacucho, Peru public school, and the importance they give it as an integral component of their teaching practice. A group of 18 male and female teachers working at the primary and secondary levels in a school in the city ofHuamanga were interviewed, representing 69% of the institution's teaching staff. Our investigation shows that the participants struggle to recognize reflection as an essential part of their professional practice, are yet to integrate it into their daily routine, and fail to include it among the attributes of good teachers. The study ends by recommending the creation of greater spaces for reflection for teachers, in order to increase their awareness of their responsibilities as educators and agents of social change.